Musketry: The Anglo Boer War experience (Historia, 2021)
The conflict between the Zuid-Afrikaanse Republic (ZAR) and Great Britain was not the first experience the British had of Boer tactics and musketry. The British had the opportunity to study the military system and approach to warfare as practised by the Boers for almost a hundred years. Still, they suffered severe losses against a "lesser" enemy who understood better the employment of the new smokeless magazine rifles. In order to understand the imbalance in the effectiveness of British and Boer firepower, the background of both the British and Boer soldiers opposing each other on the battlefields of southern Africa is illustrated. In doing so the author draws a comparison between the British soldier and his Boer opponent.
Keywords: Mounted guards; Anglo-Boer War; Military history; History; Battles of the Black Week; Musketry; Firepower; British Forces; Boer forces